ESG and Value Creation in Private Equity Investments: Analysing the Effects - Kaul, Sahib (Asian Journal of Interdisciplinary Research, 2023)
The present research evaluates the influence of Environmental, Social, and Governance (ESG) standards on the returns of private equity and explores the methods employed by private equity enterprises to incorporate ESG criteria into their investment choices. The research additionally identifies the ESG factors that are deemed most significant by private equity enterprises and scrutinises the possible advantages and disadvantages of ESG investment in the private equity sector. The present study employed a mixed-methods design, comprising a quantitative investigation of private equity returns and a qualitative exploration conducted with private equity firms. The research proposes that private equity enterprises ought to contemplate the incorporation of ESG standards into their investment assessments as a means of attaining superior returns and more effectively mitigating risk. Additional investigation is required to examine the influence of distinct ESG factors on private equity gains and to establish uniform gauges for assessing ESG accomplishments within the private equity sector.